Raters’ Judgments Of Responsibility To A Sexual Harassment Accusation From A Dissolved Workplace Romance - The Impact Of Ethics And Belief In Just World - PHUN SU MIN, CAROLYN (2004)
This present study is intended to examine judgments of responsibility and recommended personnel actions regarding a sexual harassment complaint whereby both the complainant and accused were previously involved with one another in a workplace romance. This study attempts to contribute to the limited literature available on this topic by studying the affects of rater’s ethics and Belief In Just World as moderating variables in the above framework.